Increased adrenocortical response to adrenocorticotropic hormone (ACTH) in sport horses with equine glandular gastric disease (EGGD). (October 2017) - Scheidegger, M.D.; Gerber, V.; Bruckmaier, R.M.; van der Kolk, J.H.; Burger, D.; Ramseyer, A.
Highlights: Increased response to adrenocorticotrophic hormone (ACTH) stimulation was associated with equine gastric glandular disease (EGGD). The results underline the role of stress in the pathophysiology of EGGD. There was no association between the presence and severity of equine squamous gastric disease (ESGD) and EGGD. There was a high prevalence of equine gastric ulcer syndrome in eventing and endurance horses. Abstract: This study tested the hypothesis that adrenocortical function would be altered in horses with equine gastric ulcer syndrome (EGUS). Twenty-six sport horses competing at national or international levels in eventing ( n  = 15) or endurance ( n  = 11) were subjected to a gastroscopic examination and an adrenocorticotropic hormone (ACTH) stimulation test. Salivary cortisol concentrations were measured before (baseline) and after (30, 60, 90, 120 and 150 min) IV ACTH injection (1 μg/kg bodyweight). Within EGUS, two distinct diseases, equine squamous gastric disease (ESGD) and equine glandular gastric disease (EGGD), can be distinguished. ESGD was diagnosed in 8/11 (73%; 95% confidence intervals [95%CI], 43–92%) endurance horses and 5/15 (33%; 95% CI, 14–58%) eventing horses. EGGD was observed in 9/11 (82%; 95% CI, 53–96%) endurance horses and 9/15 (60%; 95% CI, 35–81%) eventing horses. The presence or severity of ESGD was unrelated to the presence or severity of EGGD. ACTH stimulation induced a larger increase in cortisol concentration in horses with moderate EGGD than in horses with mild EGGD. Cortisol concentration during the entire sampling period (total increase in cortisol concentration during the entire sampling period [dAUC], 31.1 ± 6.4 ng/mL) and the highest measured concentration at a single time point (maximal increase in cortisol concentration [dMAX], 10.3 ± 2.3 ng/mL) were increased ( P  = 0.005 and P  = 0.038, respectively), indicating that horses with glandular gastric disease exhibited increased adrenocortical responses to ACTH stimulation. These results suggest that EGGD might be associated with an enhanced adrenocortical sensitivity. Further investigations are warranted to confirm the association between adrenocortical sensitivity and EGGD and to elucidate the pathophysiological mechanisms involved.